Atsinaujinusio šlapimo nelaikymo gydymas minimaliai invaziniu būdu: klinikinis atvejis - Černiauskienė, Aušra; Dulko, Justyna (Lietuvos chirurgija, 2016)
Stress urinary incontinence is the most common type of urinary incontinence. It is described as involuntary leaking of urine during physical activity, coughing or sneezing. Urinary incontinence can lead to physical, psychological, sexual, social or economic problems. There are many treatment options but good results are not always achieved, therefore, recurrent urinary incontinence is a common problem. According to the literature, a surgical treatment of urinary incontinence is effective up to 20% of all cases. Suburethral sling implantation operations are the first choice treatment for the recurrent urinary incontinence. We present a case of a woman who underwent 3 operations. In 2012, she was diagnosed with vesicocele and chronic perineal laceration, anterior colporrhaphy and colpoperineoplasty was made. After the surgery, stress urinary incontinence remained. In 2014, transobturator tape implantation was performed. Although postoperative period was uneventful, operation was not effective. In 2015, tension-free vaginal tape procedure was performed. Urinary incontinence disappeared, no residual urine was observed. A properly selected operative technique helps to manage the recurrent urinary incontinence and improves the quality of life. Synthetic suburethral sling implantation operation is an effective procedure for recurrent stress urinary incontinence.